Estimation of kinetic parameter using Aspen Plus on the transesterification of palm oil with methanol to produce fatty acid methyl ester / Nur Alwani Ali Bashah ... [et al.] - Ali Bashah, Nur Alwani; Razali, Wan Muhamad Zyaid; Wan, Zuraida; Rohman, Fakhrony Sholahudin (Universiti Teknologi MARA, Pulau Pinang, 2022)
Fatty acid methyl ester (FAME) is a renewable energy, mainly produced by transesterification of methanol (MeOH) and triglyceride (TG) with the aid of catalyst. The aims of this study are to estimate the kinetic of FAME production via transesterification of TG using Aspen Plus® simulator V10.3. and investigate the influence of process variables, i.e. effect of methanol: triglyceride (MeOH:TG) molar ratio and reaction temperature towards FAME production and TG conversion via sensitivity analysis. The transesterification reaction was modeled in Aspen Plus®V10.3 using stoichiometric reactor (RSTOIC) and continuous stirred tank reactor (RCSTR). In kinetic study, the reaction rate constant was determined using design spec at various reaction temperature. The reaction rate constant, K values that is predicted from the comparison study were 0.0147 s-1, 0.0661 s-1 and 0.4674 s-1 at reaction temperatures of 433.15 K, 453.15 K and 473.15 K respectively. Thus, the predicted activation energy (E) was 146.833 kJ/mol while pre-exponential factor (k) was 6.83 × 1015. In sensitivity analysis, the result showed increased MeOH:TG ratio reduced the TG conversion and FAME production. On the other hand, increased temperature caused the FAME production to increase due to high conversion of TG.